Analisis Literasi Keuangan dan Faktor Demografi: Studi Pada Pasangan Muda - Sri Mendari, Anastasia; Soejono, Fransiska; Fitria, Irin (Catholic University Musi Charitas, 2022)
This study aims to describe financial literacy based on demographic factors. The respondents involved were 401. Data collection using questionnaires. Data analysis uses crosstabulation. Financial literacy uses index financial literacy calculations which are divided into two parts, namely basic financial literacy and advanced financial literacy. Demographic factors consist of gender, age, occupation, years of service, income, and education. The results showed that they who had more income were known to have better basic and advanced financial literacy. Some interesting things were found related to the continued financial literacy of young couples, namely men who are better than women, the more age the better the literacy, the better the entrepreneurial literacy compared to those who work as employees, those who have a longer working period and Higher education has better financial literacy. Keyword: demography, financial litearcy, gender, age, job